Clinical aspects of reconstruction of the lower third of the leg with fasciocutaneous flap based on peroneal artery perforators - Terzić, Zoran; Djordjević, Boban (Vojnosanitetski pregled, 2013)
Background/Aim. Fasciocutaneous flaps are tissue flaps that include the skin, subcutaneous tissue and underlying fascia, and are based on the septocutaneous system of blood vessels. They have a number of characteristics that give them an advantage in many cases, especially in treatment of lower extremity defects. The aim of this study was to clinically analyse the outcomes of patients surgically treated with a. peroneae perforator-based reverse flaps of the lower leg. Methods. This prospective study was conducted on a group of 22 patients with tissue defects in the lower third of the lower leg and foot. All the 22 patients underwent standard diagnostic procedures and the preoperative preparation for spinal anesthesia. During the surgery, the location of the recipient site with a future flap and an accompanying vascular stem was marked. Having prepared the recipient site in accordance with the surgical principles, the lobe was prepared, rotated and positioned in the defect region. Results. The proportion of male to female patients in our study group was 19 (86%) to 3 (14%), respectively. The maximal defect frequency (14 or 63%) was found in the age group of 30–50 years, i.e. working-age people. Trauma in 16 (72%) of patients was the most common reason for surgical treatment. The most common defects our patients had were found in the distal third of the leg (5, 22%), medial malleolus (4, 18%), the dorsum of the foot (3, 13%) and the foot (4, 18%). The number of lobes (18, 81%) applied in the course of our clinical study was statistically more significant (p < 0.05) than the number of lobes applied along with the skin autografts (4, 19%). During the final follow-up of the applied lobes, 6 (27.2%) of early and 2 (9%) of late complications were observed, making a total of 36.2% of complications occurring in the applied lobes, of which only 1 was lost. Conclusion. Clinical application of a.suralis superficialis mediani-based reverse flap is justified by a high percentage (95.5%) of preserved lobes. Functional recovery of Achilles tendon injuries treated with the fasciocutaneous flap appeared to be effective. The results obtained during the clinical investigation can be very helpful in using this flap more optimally and more often in a wide range of different reconstructive surgical procedures in the field of plastic surgery.